Evaluating the impact of hydrogen peroxide on the phytoplankton community: a bench scale study - Rocha, Maria Aparecida Melo (2020)
Due to the ability to produce toxic (cyanotoxins) and non-toxic (metabolites that provide odor and flavor to water) secondary metabolites, the presence of cyanobacteria in waters destined for public supply must be controlled. However, the removal of these microorganisms in water treatment plants is a significant challenge, thus requiring alternative treatment techniques. One of these techniques is in-situ pre-oxidation using hydrogen peroxide (H2O2). In addition to acting selectively on cyanobacteria, this compound dissociates into water and oxygen, leaving no toxic by-products in the water. Although several studies have evaluated the effect of this oxidant on the phytoplankton, many have evaluated its performance only on species grown in the laboratory, not evaluating the effect on different species of phytoplankton in a tropical reservoir. Besides, there is still a knowledge gap when it comes to bench-scale studies considering the long-term impact of hydrogen peroxide on the regrowth of organisms from freshwater environments. Therefore, this thesis aims to evaluate the impact caused by different concentrations of H2O2 on the phytoplankton of a tropical reservoir and to verify whether the methodology used to evaluate the regrowth of the organisms is suitable and efficient. It was observed that H2O2 was efficient in suppressing cyanobacteria for up to seven days after its application, after analyzing the variation in the chlorophyll concentration of different phytoplankton groups. It was observed by the values of cell density counts that H2O2 caused a significant decrease (p < 0.05) in the total cell density only for the concentration of 2 mg.L-1 and not for the concentrations of 5 and 10 mg.L-1. It is noteworthy that Planktothrix sp., which was highly resistant to this oxidant since its cell density remained in the order of 105 cells.mL-1 after the application of H2O2. However, further studies on the structure of Planktothrix sp. and its possible defense features are needed. As for the methodology that evaluates the organisms regrowth, for 30 days, it is necessary to use jars of higher capacity and more intense light, probably around 40 μmol.m-2 s-1. The experiments showed that the phytoplankton cell density count was not appropriated for a fast post-treatment analysis of the impact of H2O2, since this method did not detect significant changes in the cell density values due to different doses of H2O2. Finally, to efficiently evaluate the growth of organisms on a bench scale, the methodology needs adjustments to provide an ideal environment for the organisms to grow. This methodology can evaluate whether H2O2 acts in the long term control of cyanobacteria, in addition to enabling the application of H2O2 on a full scale, through in-situ pre-oxidation.